Flabelliderma cinari (Polychaeta: Flabelligeridae), a new species from the Eastern Mediterranean - KARHAN, S.U.; SIMBOURA, N.; SALAZAR-VALLEJO, S.I. (Mediterranean Marine Science, 2012)
A new species of flabelligerid polychaete, Flabelliderma cinari, is described from the Turkish coast of the Eastern Mediterranean Sea. This represents the first occurrence of the genus Flabelliderma in the Mediterranean. Flabelliderma cinari sp. nov. is closely allied to F. claparedei in having dorsal tubercles of two different sizes; however, these species differ in the relative shape and number of dorsal tubercles, the number of capillaries per fascicle in the notopodia and the shape of the curved distal articles in the neuropodial hooks.